Templated electrodeposition as a scalable and surfactant-free approach to the synthesis of Au nanoparticles with tunable aspect ratios. Issue 11 (13th May 2022) - Abbondanza, Giuseppe; Larsson, Alfred; Linpé, Weronica; Hetherington, Crispin; Carlá, Francesco; Lundgren, Edvin; Harlow, Gary S.
Abstract : We synthesised ordered arrays of low-dimensional Au with controllable aspect ratio and morphology. The surfactant-free fabrication, the size-dependent strain state and the twinning defects could be beneficial for catalysis. Abstract : A high-throughput method for the fabrication of ordered arrays of Au nanoparticles is presented. It is based on pulsed electrodeposition into porous anodic alumina templates. In contrast to many synthesis routes, it is cyanide-free, prior separation of the alumina template from the aluminium substrate is not required, and the use of contaminating surfactants/capping agents often found in colloidal synthesis is avoided. The aspect ratio of the nanoparticles can also be tuned by selecting an appropriate electrodeposition time. We show how to fabricate arrays of nanoparticles, both with branched bases and with hemispherical bases. Furthermore, we compare the different morphologies produced with electron microscopies and grazing-incidence synchrotron X-ray diffraction. We find the nanoparticles are polycrystalline in nature and are compressively strained perpendicular to the direction of growth, and expansively strained along the direction of growth. We discuss how this can produce dislocations and twinning defects that could be beneficial for catalysis.